An integrative study to identify novel scaffolds for sphingosine kinase 1 inhibitors - Vettorazzi, Marcela Cristina (2017)
Fil: Vettorazzi, Marcela Cristina. Universidad Nacional de San Luis. Facultad de Química, Bioquímica y Farmacia. Instituto Multidisciplinario de Investigaciones Biológicas; Argentina.